Merit System dalam Pengisian Jabatan Pimpinan Tinggi di Kabupaten Mamuju Tengah - Salman, Rara Novrayanti (Gorontalo Journal of Government and Political Studies, 2019)
Merit System in ASN Act 2014 is defined as qualification, competence and performance of employees. This study aimed to describe and analyze the filling of first high leadership positions in Central Mamuju Regency, West Sulawesi was seen from merit system. The data collection in this research was done by observation, interview, and documentation. Data were analyzed by using qualitative analysis. The results showed that the overall merit system had not been applied in the filling of high-ranking leadership position in Central Mamuju Regency, West Sulawesi. The filling of the top management positions by the Government of Central Mamuju Regency, West Sulawesi was conducted in Job Fit and Inauguration. However, the procedure for filling in the top leadership position in Central Mamuju Regency had resembled merit system. It was because based on Letter of Minister of State for State Apparatus Empowerment No. B/3116/M.PANRB/09.2016, stated that the positions auction may be done by sharing the same colleges or other assessors such as Institute of State Administration and State Personnel Board, and this had also been done by Central Mamuju Regency Government. In addition, the principles of merit system such as education and training, experience, skills, ethics and work performance are also contained and elaborated in 42 items of assessment made by Head of Organization and Management and State Personnel Board of Central Mamuju Regency. One of the reasons had hot been implemented the merit system as a whole in Central Mamuju Regency was because the current Secretary off Office was skill filled by task executive, there is no definitive Secretary yet. In addition, the budget issue was also another reason, because for one of the Regional Device Work Unit only if the merit system requires Rp. 7.000.000. Merit system dalam Undang-Undang ASN 2014 diartikan sebagai kualifikasi, kompetensi dan kinerja pegawai. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis pengisian jabatan pimpinan tinggi pratama di Kabupate Mamuju Tengah Sulawesi Barat dilihat dari merit system. Pengumpulan data dalam penelitian ini dilakukan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa secara keseluruhan merit system belum diterapkan dalam pengisian jabatan pimpinan tinggi pratama di Kabupaten Mamuju Tengah Sulawesi Barat. Pengisian jabatan pimpinan tinggi pratama yang dilaksanakan oleh Pemerintah Kabupaten Mamuju Tengah dilakukan secara Job Fit dan Pengukuhan. Akan tetapi, prosedur dalam pengisian jabatan pimpinan tinggi pratama di Kabupaten Mamuju Tengah telah menyerupai merit system. Hal ini karena berdasarkan surat edaran MENPAN Nomor B/3116/M.PANRB/09/2016, menyatakan bahwa lelang jabatan itu boleh dilakukan dengan sharing sama perguruan tinggi atau assessor lainnya seperti LAN dan BKN, dan hal ini pun telah dilakukan oleh Pemerintah Kabupaten Mamuju Tengah. Selain itu, prinsip merit system seperti pendidikan dan pelatihan, pengalaman, keterampilan, etika dan prestasi kerja juga termuat dan dijabarkan dalam 42 item penilaian yang di buat oleh Kabag Ortala dan BKD Kabupaten Mamuju Tengah. Salah satu alasan belum diterapkannya merit system secara keseluruhan di Kabupaten Mamuju Tengah adalah karena jabatan Sekda saat ini masih diisi oleh pelaksana tugas, belum ada Sekda definitif. Selain itu, masalah anggaran juga merupakan alasan lainnya, karena untuk 1 SKPD saja jika harus merit system membutuhkan dana Rp.7.000.000.